Response timing and muscular coordination in fencing: A comparison of elite and novice fencers - Williams, L. R.; Walmsley, A. (Journal of Science and Medicine in Sport, 2000)
Reaction time (RT), movement time (MT), total response time (RMT) and accuracy of elite and novice fencers was studied under three levels of target choice (single-, two- and four-targets) with three variations of movement distance (short, medium and long lunge). In addition, electromyographic activity (EMG) of selected upper and lower limb muscles was used to compare the two groups. The elite subjects were faster for RT and RMT and displayed a higher level of accuracy. The hypothesis that increasing choice would cause increases in RT was not upheld. Except for some differentiation between the short and the two longer distances, the effects of movement distance were not marked. Qualitative and quantitative analysis of EMG revealed the high consistency of response patterns within subjects and highlighted the synergistic roles of selected muscles in distinguishing between elite and novice fencers. These findings confirm that differences in the technical skill of fencers can be distinguished in the laboratory through a combination of response timing measures in association with measures of muscle action. They also draw attention to practical implications for individual skill assessment and training. Analysis of pre-movement muscle activity provided moderate support for the hypothesis that it was part of a single control process and indicates that a dual process can involve both the maintenance of postural stability and the generation of movement. It is suggested that different movement contexts can lead to different levels of coordination between the system controlling posture and that controlling movement.